Profile of autopsy cases in central level hospital of Nepal. A retrospective study of two years - Baral, Madan Prasad (Asian Journal of Medical Sciences, 2020)
Background: Autopsy is a systemic scientific examination of dead body by the help of which information about the cause of death can be obtained in unnatural death cases. Various countries have to follow their own law to perform an autopsy. Aims and Objectives: This study aims to analyze the pattern of autopsy cases with manner and various cause of death, which was conducted in central level hospital. Material and Methods: It is a retrospective type record based study conducted in two years period at central level hospital of Nepal in 775 corpse. Result: Out of 775 cases of autopsy, 465 males and 310 females which accounts 60% of male and 40% of female cases.In context of age group the highest number of cases came for autopsy is 21-30 years of age group which accounts 39.35% of total cases followed by 31-40 years of age group and accounts 31.61% of total cases. Suicidal death cases are the highest number of cases presented 59.09% for autopsy. This is followed by accidental deaths of 27.48% and thenundetermined 9.29% and lastly homicidal 4.12%. Regarding the cause of death blunt injury cases are highly presented with 44.54% and the firearm injury cases are presented very less with only 0.25% in total 775 cases. Conclusion: In the current study it can be concluded that the Medico legal autopsy was performed in 775 corpse in a period of 2 years at central level hospital where the Male cases are predominated over Female with presence of the highest number of cases in an age group of 21-30 years. Suicidal manner of death cases are highest in number with the leading cause of death as Blunt injury.